Analysis on the Influence of Inflation, Ship’s Call, And Unloading Cost towards General Cargo Inter-Insular Ships in Surabaya Port - Cahyono, Rosadiro (Archives of Business Research, 2016)
Indonesia is an archipelago nation since statistic shows that Indonesia consists of more than 13,000 islands, it is natural for inter-insular ships to play a dominant role in connecting one island to another supported by other local ships. In comparison, the inter-insular ships docking and unloading in Surabaya’s port, as well as the Ship’s call and DWT Ship’s call, outweighs the local ships. In 2002-2006, inter-insular ships’ unloaded 8,791 units of 28,739,718 tons; 7,820 units of 31,021,731 tons; 8,277 units of 25,496,489 tons; 9,595 units of 22,793,415 tons; and 9,345 units of 23,250,003 tons. On the other hand, in the same period of time, local ships only unloaded 1,204 units of 158,877 tons; 901 units of 157,663 tons; 1,023 units of 126,111 tons, 1,124 units of 403,826 tons; 919 units of 176,550 tons. This research wants to analyze the number of inter-insular ships, based on several internal and external variables: Unit Ship’s Call (X1), DWT Ship’s Call (X2), Inflation (X3), and Unloading Cost (X4). The research was done in Surabaya, Indonesian port during 2014-2015. Keywords: Influence of inflation, ships call, unloading cost